Unique Patient Issues: Early Interventions and Management - Combelles, Catherine (Seminars in Reproductive Medicine, 2012)
Patient cases that present with recurring fertilization failure or complete abnormality in either the oocytes or sperm before fertilization are uncommon, yet they are devastating. This review presents several such instances, including oocyte maturation blocks, empty follicle syndrome, oocyte activation failures, defects in sperm phospholipase C isoform ζ, sperm structural anomalies, spontaneous oocyte activation, and unexplained cases. Diagnostic efforts have not only provided insight into possible etiologies but also have helped manage such challenging cases. Interventions may comprise cellular, molecular, or genetic analyses of gametes, as well as functional assays and/or modified treatment strategies. Consequently, infertility professionals can increasingly rely on evidence-based counseling with respect to prognosis and treatment options.
Keywords: fertilization failure; maturation arrest; oocyte factors; total recurrent failure; unexplained infertility